Relationship of Body Mass Index to Alcohol Consumption in College Freshmen - Mary A. Nies; Linman Sun; Donna Kazemi; Amy Carriker; Jacek Dmochowski (The Scientific World Journal)
Objective. Assess the relationship between body mass index (BMI) and drinking in college freshman. Method. College freshman (N=199) at a university completed the drinking questionnaires. Drinking amount and the alcohol problem index (RAPI) served as outcomes, and BMI was the independent variable. Results. RAPI scores were associated with gender, amount of drinking, and BMI (P<0.001, F=13.44). Increase of RAPI with drinking amount was larger for females (slope=0.06) than for males (slope=0.03). Conclusion. This information can be helpful when providing health promotion strategies to college students regarding nutrition modifications that would be most beneficial for their health.